2018
DOI: 10.1111/jfcj.12119
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disproportion in Juvenile Justice Contact

Abstract: Youth from disadvantaged neighborhoods have been found to have greater rates of justice system involvement than other youth, as well as differential treatment at multiple points in the justice system process. This neighborhood disproportion stems from different rates of lawbreaking and system bias and has important implications for long‐term negative outcomes associated with juvenile justice contact. Clarity in the state of knowledge on this topic is essential to guide researchers and policymakers in addressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(184 reference statements)
1
2
0
Order By: Relevance
“…In the same way that we observe place-based crime concentrations, penologists have likewise observed that corrections outcomes (such as sentencing trends and re-entry and reoffending measures) demonstrate spatial aggregations ( Rose and Clear, 1998 ; Clear et al, 2003 ; Clear, 2005 ; Sharlein and Engstrom, 2018 ), influenced by features of those communities ( Baglivio et al, 2015 ; Chamberlain and Wallace, 2016 ). Given these associations, it is sensible that probation and parole officers occasionally utilize techniques that are opportunity-focused, such as through efforts to limit supervisees’ unstructured leisure time or associations with risky peers ( Miller, 2014 ; Miller et al, 2015 ).…”
Section: Literature Reviewsupporting
confidence: 76%
“…In the same way that we observe place-based crime concentrations, penologists have likewise observed that corrections outcomes (such as sentencing trends and re-entry and reoffending measures) demonstrate spatial aggregations ( Rose and Clear, 1998 ; Clear et al, 2003 ; Clear, 2005 ; Sharlein and Engstrom, 2018 ), influenced by features of those communities ( Baglivio et al, 2015 ; Chamberlain and Wallace, 2016 ). Given these associations, it is sensible that probation and parole officers occasionally utilize techniques that are opportunity-focused, such as through efforts to limit supervisees’ unstructured leisure time or associations with risky peers ( Miller, 2014 ; Miller et al, 2015 ).…”
Section: Literature Reviewsupporting
confidence: 76%
“…Another potential explanation of this finding is that racial minorities may be subjected to differential treatment by various juvenile and criminal justice actors. Some research has suggested that minority youth are subjected to increased surveillance by law enforcement and increased supervision by the juvenile court (Sharlein & Engstrom, 2018), which may cause minority youth to experience increases in risk score in comparison to White youth. If the increase in risk score is the result of differential treatment, then more research and policy changes are needed to identify how to fairly evaluate justice-involved youths’ risks and needs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, youth within this domain may often come from disadvantaged neighborhoods, which may increase the chance that individuals come into contact with the justice system. Further, evidence has uncovered that youth in disadvantaged neighborhoods may be exposed to additional surveillance by law enforcement (Sharlein & Engstrom, 2018). Practitioners should focus on treating these youth as other lower risk youth, even though the history domain pushes the average score of these youth toward moderate risk to avoid the potential iatrogenic or labeling effects of the juvenile justice system (Bernberg et al, 2006; Lowenkamp & Latessa, 2004).…”
Section: Discussionmentioning
confidence: 99%